The Effectiveness of Physiotherapy Program for the Children with Visual Impairment and Additional Disabilities: A Case Series - LEBLEBİCİ, Gökçe; AYYILDIZ, Emine; RINDERMANN, Sylvia (Archives of health science and research, 2024)
Objective: Children with visual impairment and additional disabilities (CVIAD) often encounter significant motor issues and health problems stemming from factors such as brain damage, early vision loss experiences, hearing loss, and a lack of tactile and cutaneous senses. Therefore, physiotherapists should provide appropriate verbal teaching and manual support to those children during treatment, but there is no evidence-based physiotherapy program for CVIAD as an early intervention. This study aimed to understand the effects of a physiotherapy program for CVIAD on the neurodevelopment of child as a part of early intervention. Methods: Two children were included in the study. The Gross Motor Function Classification System (GMFCS), Pediatric Evaluation of Disability Inventory (PEDI), Functional Independence Measure (WeeFIM), and The Goal Attainment Scale (GAS) were used to determine the neurodevelopmental changes in the cases. The children were included in the 12-week physiotherapy program, which specialized in verbal and tactile stimulations. Results: The PEDI self-care and social function subtest scores and the WeeFIM score of the case 2 increased after the intervention. Conclusion: The physiotherapy program enriched with child-specific tactile and verbal stimuli and toys suitable for these children will contribute to motor and sensory development. Cite this article as: Leblebici G, Ayyıldız E, Rindermann S. The effectiveness of physiotherapy program for the children with visual impairment and additional disabilities: A case series. Arch Health Sci Res. 2024;11(2):107-111.